2010
DOI: 10.3892/ijo_00000751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rapamycin, an mTOR inhibitor, on radiation sensitivity of lung cancer cells having different p53 gene status

Abstract: Abstract. Activation to a large extent of the phosphatidylinositol 3-kinase (PI3K)/Akt pathway and mutations in the p53 gene are involved in lung cancer therapeutic resistance. The mammalian target of rapamycin (mTOR) acts as a downstream effector for Akt. Activation of the Akt/mTOR signal is a contributing factor to decreased radiation sensitivity. The purpose of this study was to examine whether the effect of rapamycin on radiation sensitivity is affected by cellular p53 gene status. Cellular radiation sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 35 publications
3
29
0
1
Order By: Relevance
“…At the concentration of 10 nM RAPA was found not to induce significant apoptosis, consistent with its cytostatic effect on cancer cell lines, as reported recently (17)(18)(19). This result indicated the significance of using a combination of low-dose RAPA with L-OHP in the clinic, in that the combined therapy led to less toxicity and better tolerability.…”
Section: Discussionsupporting
confidence: 65%
“…At the concentration of 10 nM RAPA was found not to induce significant apoptosis, consistent with its cytostatic effect on cancer cell lines, as reported recently (17)(18)(19). This result indicated the significance of using a combination of low-dose RAPA with L-OHP in the clinic, in that the combined therapy led to less toxicity and better tolerability.…”
Section: Discussionsupporting
confidence: 65%
“…The blockade of the mTORC1 can activate the ULK1 complex and promote the interaction with the PtdIns3K complex which is necessary for the formation of new autophagosomes (47). Several studies have reported on the positive effects of mTOR inhibitor on sensitizing cancers to radiation therapy and chemotherapy in lung cancer, pancreatic carcinoma cells and esophageal carcinoma cells (48)(49)(50)(51).…”
Section: Dna Damage Repair and Autophagymentioning
confidence: 99%
“…Increased mTOR phosphorylation is frequently observed alongside activated Akt in NSCLC and dysregulation of mTOR contributes to lung cancer progression [18,19]. Several studies have shown that mTOR inhibition enhances the cytotoxic effects of chemotherapeutic agents and radiation in cancer [20][21][22][23]. These observations led to the evaluation of the antiproliferative effects of rapamycin and its derivatives (rapalogs), including the cell cycle inhibitor (CCI)-779 (temsirolimus), RAD001 (everolimus), and AP23573 (deforolimus), in malignant neoplasms [24].…”
Section: Introductionmentioning
confidence: 99%